(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article is devoted to the analysis of the costs of commercial banks and ways to achieve financial stability. In it, the structure of the costs of banks associated with operational, administrative, technological and credit risks is studied in depth. Modern methods of cost optimization are analyzed, including digitization, automation and strategies to improve employee efficiency. Cost effective management shows that it increases the profitability of banks and is an important factor in ensuring financial stability. On the example of commercial banks of Uzbekistan, specific problems and opportunities for reducing costs in local conditions are considered.